Manajemen Layanan Peserta Didik Inklusif di Kota Palangka Raya - Desi Erawati; Ana Kamerloh Dian; Nurwidiantoro Nurwidiantoro (LP2M IAIN Palangka Raya, 2017)
Service management becomes important to provide a good service to the learners in general, especially on learners inclusive. The focus of the issues examined is how the pattern of service management, especially learners inclusive in SMAN 4 Palangkaraya and how the factors that hinder the management services on learners inclusive, and are there any obstacles in providing services to students at SMAN 4 Palangkaraya inclusive. This study used a qualitative approach, using a sampling technique is purposive sampling. Our research findings show that the management services are basically all the same, but no differences were seen, that there are some things that are found such as recruitment, selection, and placement in inclusive classroom learners in the classroom. Factors inhibiting the service management process inclusive learners there are two internal and external factors. School principals, in this case, seek to follow up on these constraints to appoint one coordinator teachers to become inclusive in the school structure, provide socialization on inclusive education to the school community, as well as monitor and evaluate the implementation of inclusive education in schools.